2010
DOI: 10.1155/2010/426804
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Interaction between Capecitabine and Warfarin Resulting in Altered Coagulation Parameters: A Review of the Literature Starting from a Case Report

Abstract: Capecitabine is an orally active prodrug of fluorouracil and is extensively used as an antineoplastic agent. It is converted to 5-Fluorouracil in the liver and tumor tissues. Warfarin is an anticoagulant agent for preventing and treating venous and arterial thrombosis and embolism and is metabolized by cytochrome P450 isoenzymes in the liver. Preclinical in vitro studies using human liver microsomes report no inhibitory effects between capecitabine and substrates of cytochrome P. However, the concomitant admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The study of downregulation of drug‐metabolizing enzymes presents a few challenges, some of which include (1) variability in drug response in human hepatocyte experiments partly due to differences in culture conditions; (2) loss of enzymatic activity in hepatocyte cultures over time; (3) lack of positive controls for downregulation; and (4) the facts that observed changes in mRNA may be due to cytotoxicity, and in vitro findings do not always translate into clinical effects . The prolonged change in pharmacokinetics observed in our study is similar to those previously reported in DDIs with warfarin and other CYP2C9 substrates, and transcriptional changes can take time to disappear. We were unable to find a suitable nonclinical model to study an event that takes this long to manifest.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The study of downregulation of drug‐metabolizing enzymes presents a few challenges, some of which include (1) variability in drug response in human hepatocyte experiments partly due to differences in culture conditions; (2) loss of enzymatic activity in hepatocyte cultures over time; (3) lack of positive controls for downregulation; and (4) the facts that observed changes in mRNA may be due to cytotoxicity, and in vitro findings do not always translate into clinical effects . The prolonged change in pharmacokinetics observed in our study is similar to those previously reported in DDIs with warfarin and other CYP2C9 substrates, and transcriptional changes can take time to disappear. We were unable to find a suitable nonclinical model to study an event that takes this long to manifest.…”
Section: Discussionsupporting
confidence: 79%
“…There have been numerous reports suggesting a drug‐drug interaction (DDI) between fluoropyrimidines and warfarin, an anticoagulant with a narrow therapeutic index widely used for prevention and treatment of thrombosis and embolism . Altered coagulation parameters and/or bleeding have been observed within several days and up to several months after initiation of capecitabine therapy in patients with concomitant warfarin, and up to 1 month after stopping capecitabine . Concomitant administration of capecitabine and warfarin was found to increase the area under the curve from time zero to infinity (AUC 0‐∞ ) and elimination half‐life of S ‐warfarin by 57% and 51%, respectively, and to reduce the apparent clearance by 36% (after 3 treatment cycles) compared with warfarin alone .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have thus reported on interactions between warfarin and fluoropyrimidine anticancer drugs, including FU, capecitabine, and S-1 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Drug packaging inserts for both capecitabine and S-1 contain warnings regarding their coadministration with warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since it is known that cancer patients have a tendency toward thrombosis, prophylactic anticoagulant therapy for cancer patients is widely accepted [5,6] and the number of cancer patients who are being treated with warfarin is increasing. However, many studies have shown that the effects of warfarin are enhanced by interaction with fluoropyrimidine anticancer drugs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. As a consequence of these reports, warnings about the combination of these drugs are included in the instructions for capecitabine and S-1.…”
Section: Introductionmentioning
confidence: 99%